Gestión de abastecimiento del Almacén Mairita de la parroquia Isla de Bejucal, cantón Baba en el período 2022. - Soto Mite, Alex Anthonny (2023)
The purpose of this case study is to present an analysis of supply management and its importance in the acquisition, storage and distribution of finished products to carry out the marketing process and thus meet the needs of customers in a timely manner and generating income for the company. The research focus is the "Almacén Mairita", a business located in the parish of Isla De Bejucal, Canton Baba, whose line of business is the sale of stationery, clothing and accessories. The results show that the distribution processes of the products that the proposed company has present a significant level in the second semester of the year 2022 with high sales, in addition to an increase in its suppliers in that period, however, the first semester presented sales that covered the expenses, but did not generate additional income. It is concluded that the customers were satisfied with the facilities and the business environment as well as the variety of designs and brands they have, but the problem was in the level of inventory turnover which presented a lower level than normal, as a result after applying the KPIs it was decided that the demand should be studied to determine which products have greater output and which are those that are sold more slowly and thus be able to improve supply management.